2017
DOI: 10.1111/1365-2745.12748
|View full text |Cite
|
Sign up to set email alerts
|

Deer‐mediated changes in environment compound the direct impacts of herbivory on understorey plant communities

Abstract: Summary In forests of eastern North America, white‐tailed deer (Odocoileus virginianus) can directly affect, via herbivory, the presence, abundance and reproductive success of many plant species. In addition, deer indirectly influence understorey communities by altering environmental conditions. To examine how deer indirectly influence understorey plants via environmental modification, we sampled vegetation and environmental variables in‐ and outside deer exclosures (10–20 years old) located in temperate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 80 publications
1
15
0
1
Order By: Relevance
“…Over a large monitoring network, covering a broad range of temperate forest ecosystems, we observed that the presence of wild ungulates enhanced species richness of the herbaceous layer. In line with Sabo, Frerker, Waller, and Kruger (), our results show that ungulate impacts on forest understory vegetation are a consequence of their effects on environmental factors but also bring to light their critical role on plant species dispersal and plant‐plant interactions. More specifically, by reducing the cover of shrub layers and dominant and palatable plant species, deer maintain an openness that enhances ground flora diversity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Over a large monitoring network, covering a broad range of temperate forest ecosystems, we observed that the presence of wild ungulates enhanced species richness of the herbaceous layer. In line with Sabo, Frerker, Waller, and Kruger (), our results show that ungulate impacts on forest understory vegetation are a consequence of their effects on environmental factors but also bring to light their critical role on plant species dispersal and plant‐plant interactions. More specifically, by reducing the cover of shrub layers and dominant and palatable plant species, deer maintain an openness that enhances ground flora diversity.…”
Section: Discussionsupporting
confidence: 90%
“…Over a large monitoring network, covering a broad range of temperate forest ecosystems, we observed that the presence of wild ungulates enhanced species richness of the herbaceous layer. In line with Sabo, Frerker, Waller, and Kruger (2017)…”
Section: Beyond Increasing Species Richness: Shifts In Species Compmentioning
confidence: 88%
“…High soil compaction alters soil hydrology and aggregation and has deleterious effects on plant vital rates, leading to physiological dysfunction, reduced water and soil nutrient absorption, and altered root respiration (Kozlowski 1999). Increased soil compaction by deer has known negative effects on forest plant abundance and diversity (Sabo et al 2017). For Arisaema, our previous work demonstrates that plant vital rates decline as abiotic site impacts by deer increases ( fig.…”
Section: Study Sitesmentioning
confidence: 97%
“…We focused on two questions: (a) how do deer affect the abundance and diversity of tree species regeneration along its height growth, and (b) what is the impact of the presence of deer on the diversity of herbaceous layer vegetation? Species composition in the herbaceous layer may be sensitive to changes in the tree species regeneration layer mediated by deer (Beguin, Pothier, & Côte, ; Sabo, Frerker, Waller, & Kruger, ; Stewart et al., ). Therefore, we also tested for the indirect influence of red deer on the diversity of shorter tree species regeneration and the diversity of the herbaceous layer through its influence on the recruitment of saplings of tree species.…”
Section: Introductionmentioning
confidence: 99%